Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-85678-5
|View full text |Cite
|
Sign up to set email alerts
|

Thigmotaxis in a virtual human open field test

Abstract: Animal models are used to study neurobiological mechanisms in mental disorders. Although there has been significant progress in the understanding of neurobiological underpinnings of threat-related behaviors and anxiety, little progress was made with regard to new or improved treatments for mental disorders. A possible reason for this lack of success is the unknown predictive and cross-species translational validity of animal models used in preclinical studies. Re-translational approaches, therefore, seek to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 86 publications
0
14
0
1
Order By: Relevance
“…Thigmotaxis or centrophobism, i.e., the tendency of animals to avoid the center area of an open field or arena and instead to spend more time in its periphery, is a behavioral response that is evolutionary conserved from Drosophila ( Besson and Martin, 2005 ; Mohammad et al, 2016 ) to zebrafish ( Colwill and Creton, 2011 ; Richendrfer et al, 2012 ; Schnörr et al, 2012 ; Pietri et al, 2013 ; Zhang et al, 2017 ; Xu and Guo, 2020 ) and mammals ( Hall, 1934 ; Denenberg, 1969 ; Treit and Fundytus, 1988 ; Prut and Belzung, 2003 ), including humans ( Walz et al, 2016 ; Gromer et al, 2021 ). Although a natural behavioral tendency across species, it has been suggested that thigmotaxis is indicative of an anxiety-like state in both larval and adult zebrafish ( Maximino et al, 2010 ; Richendrfer et al, 2012 ; Schnörr et al, 2012 ; Pietri et al, 2013 ; Zhang et al, 2017 ; Abreu et al, 2020 ; Xu and Guo, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thigmotaxis or centrophobism, i.e., the tendency of animals to avoid the center area of an open field or arena and instead to spend more time in its periphery, is a behavioral response that is evolutionary conserved from Drosophila ( Besson and Martin, 2005 ; Mohammad et al, 2016 ) to zebrafish ( Colwill and Creton, 2011 ; Richendrfer et al, 2012 ; Schnörr et al, 2012 ; Pietri et al, 2013 ; Zhang et al, 2017 ; Xu and Guo, 2020 ) and mammals ( Hall, 1934 ; Denenberg, 1969 ; Treit and Fundytus, 1988 ; Prut and Belzung, 2003 ), including humans ( Walz et al, 2016 ; Gromer et al, 2021 ). Although a natural behavioral tendency across species, it has been suggested that thigmotaxis is indicative of an anxiety-like state in both larval and adult zebrafish ( Maximino et al, 2010 ; Richendrfer et al, 2012 ; Schnörr et al, 2012 ; Pietri et al, 2013 ; Zhang et al, 2017 ; Abreu et al, 2020 ; Xu and Guo, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of virtual environments has allowed for additional assessments of humans on similar learning and memory tasks used in rodents. Using a virtual open field task, Gromer et al (2021) investigated human movement behavior as analogous to animal studies and showed a strong similarity across species ( Gromer et al, 2021 ). Biedermann et al (2017) re-translated the elevated plus maze to a human virtual reality test and reported the predicted open-arm avoidance ( Biedermann et al, 2017 ).…”
Section: Reverse Translationmentioning
confidence: 99%
“…This approach should build a more solid basis to develop novel tools to help clinical diagnosis and maximise the predictive validity of AAC preclinical paradigms used to test pharmacological interventions for humans (Belzung and Lemoine, 2011 ). Cross-species behavioural tests to assess AAC mainly exploit paradigms of exploration (Gromer et al ., 2021 ). Mammals' functioning is indeed based on an innate exploratory drive for territorial recognition, food supply and reproduction, which are in turn associated with a significant reward (Kidd and Hayden, 2015 ).…”
Section: Cross-species Paradigms To Assess Aacmentioning
confidence: 99%